Evaluation of Ultrasound-Guided Erector Spinae Plane Block and Oblique Subcostal Transversus Abdominis Plane Block in Laparoscopic Cholecystectomy: Randomized, Controlled, Prospective Study - Tulgar, Serkan (Anesth Essays Res, 2019)
BACKGROUND: Oblique subcostal transversus abdominis plane block (OSTAP) is a recently described regional anesthetic technique used in upper abdominal surgeries such as laparoscopic cholecystectomy (LC). Erector spinae plane block (ESPB) has also been reported for postoperative analgesia in LC. AIM: We aimed to compare the effectiveness of OSTAP and ESPB in providing postoperative analgesia in patients undergoing these surgeries. SETTING AND DESIGN: This study was designed as a double-blinded, prospective, randomized, efficiency study in a tertiary university hospital, postoperative recovery room, and ward. MATERIALS AND METHODS: A total of 72 patients were recruited and 60 patients were randomized into three equal groups (ESPB, OSTAP, and control group). Pain intensity between groups was compared using Numeric Rating Scale (NRS) scores. In addition, consumption of paracetamol and tramadol and additional rescue analgesic requirement were measured. Standard multimodal analgesia was performed in all groups, while ESPB block was also performed in Group ESPB and OSTAP block was also performed in group OSTAP. STATISTICAL ANALYSIS USED: Descriptive statistics were expressed as mean ± standard deviation. Independent t-test, Mann–Whitney U-test, Chi-square test, Fisher's exact test, Shapiro–Wilk test, one-way ANOVA, and post hoc Tukey's analysis were used for statistical analysis. RESULTS: NRS was lower in block groups during the first 3 h. There was no difference in NRS scores at other hours. Analgesic consumption and rescue analgesic requirement were lower in groups ESPB and OSTAP when compared to those of control group. Block groups were similar. CONCLUSION: Bilateral ultrasound-guided ESPB and OSTAP performed at the end of LC lead to akin analgesia requirement and improve the quality of multimodal analgesia.